Microstructure and wear properties of selective laser melted WC reinforced 18Ni-300 steel matrix composite. (August 2018) - Kang, Nan; Ma, Wenyou; Li, Fuhai; Liao, Hanlin; Liu, Min; Coddet, Christian
Abstract: In this work, a novel high-wear-resistant dense WC/18Ni-300 maraging steel matrix composite (99.6%) was manufactured by selective laser melting from power mixture of WC and maraging steel. The microstructural analysis indicates that the WC particle was either partially or fully melted during SLM process with a homogenous distribution. Moreover, a phase transition from α-Fe to γ (Fe, Ni) appears after adding WC reinforcement. The TEM was used to investigate the interfacial structure between WC and maraging steel with focus on the elemental distribution, which indicates the W element was diffused via grain boundary and hold back the α to γ transition. Microhardness and ball-on-disc test are employed to determine their wear properties. The results show that the wear resistance of SLM processed composites is much higher than that of SLM processed maraging steel. Graphical abstract: Image 1 Highlights: Both the SLMed maraging steel and composite show high relative density. A phase transition from bcc martensite to fcc austensite with the addition of WC. Metallurgical bonding between reinforcement and matrix is realized by diffusion. Wear resistance is improved by adding WC due to its high microhardness and wear resistance.